EFFICIENT AND FACILE SYNTHESIS OF HYDROXY-FUNCTIONALIZED HEXAGONAL BORON NITRIDE NANOSHEETS BY ION-ASSISTED LIQUID PHASE EXFOLIATION METHOD - Gülşah Yaman Uzunoğlu (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi)
Hexagonal boron nitride (h-BN) nanosheets have attracted significant attention due to their unique mechanical, thermal, and electronic properties. Their biocompatibility, thermal conductivity, chemical stability, and versatility make them indispensable in cutting-edge technologies. Hydroxy-functionalized h-BN nanosheets (h-BNNS-OH) exhibit immense potential in various applications, including electrochemical energy storage, drug delivery systems, and heat spreaders in thermal management systems. This study focuses on the hydrothermally ion-assisted liquid-phase exfoliation of h-BN powder to produce few-layer h-BNNS-OH. The exfoliation process involves hydrothermal treatment of bulk h-BN in the presence of concentrated aqueous solution of KOH and NaOH at 180 °C, followed by sonication for dispersion of h-BNNS-OH in water. Characterization of h-BNNSs was performed using powder X-ray diffraction (XRD), Raman spectroscopy, Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). The resulting exfoliated h-BNNSs are hydroxyl-functionalized on their surface. This study demonstrates the effectiveness of the successive execution of the hydrothermal treatment in the presence of excess alkali metal hydroxides and probe sonication as a facile and efficient exfoliation process, resulting in dispersions of h-BNNS-OH in water with remarkably high stability (beyond 9 weeks) and high product yield (17 %) at only one exfoliation cycle.